Portable traffic light system / Mohamad Fairuz Ahmad and Muhammad Abrar Abdul Hamid - Ahmad, Mohamad Fairuz; Abdul Hamid, Muhammad Abrar (2015)
This thesis is about the design and development of the prototype of portable traffic light system with one indicator display instead of three. This thesis includes the review of current traffic light system with three indicators which includes the calculation for timer of the traffic light based on the speed and the length of the vehicle. This portable traffic light prototype is not designed to be used at the junction as normal traffic light but to be used as temporary traffic flow control when a stretch of two ways road or two lanes is under circumstances of only one lane can be used. Therefore this traffic light will allow the flow of traffic in one direction alternatively. There will be only two poles of this traffic light called main pole and sub pole. Firstly, a lot of researches and surveys conducted to get as much as possible information on how to design the best prototype ever. The research also includes the study of the hardware used in the prototype. The design begins with the decision of the hardware to be used so that software can be designed afterward. The software is designed using flow chart before write the program codes using PIC assembly language. Simulation is used to help debugging the software and to ensure the success of software design. Then the real development is started with hands on activities to build the modules for the traffic light. Generally, there are five modules build. These modules are voltage regulator, controller, relay, user control panel and lastly traffic light indicator. Voltage regulator is designed using power transistor 2N3055 because the prototype consumes current more than the conventional 7805 could support. The controller used PIC18F4550 microprocessor which then connected to relay module to drive the high current to traffic light indicator module. The user control panel module is just added feature to allow user to set timer for green time of the traffic light. To satisfy the portable functionality, this prototype will run on battery.